2018
DOI: 10.1111/cdev.13154
|View full text |Cite
|
Sign up to set email alerts
|

A Family Focused Intervention Influences Hippocampal‐Prefrontal Connectivity Through Gains in Self‐Regulation

Abstract: The stressors associated with poverty increase the risks for externalizing psychopathology; however, specific patterns of neurobiology and higher self‐regulation may buffer against these effects. This study leveraged a randomized control trial, aimed at increasing self‐regulation at ~11 years of age. As adults, these same individuals completed functional MRI scanning ( M age = 24.88 years; intervention n = 44; control n = 49). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
3
14
0
Order By: Relevance
“…For any regions above this threshold, mean functional connectivity estimates were then extracted by averaging across every voxel in each regional cluster. These procedures are in keeping with other past reports from our group (e.g., Hanson et al, 2019).…”
Section: Methodssupporting
confidence: 88%
“…For any regions above this threshold, mean functional connectivity estimates were then extracted by averaging across every voxel in each regional cluster. These procedures are in keeping with other past reports from our group (e.g., Hanson et al, 2019).…”
Section: Methodssupporting
confidence: 88%
“…Critically, the family context during adolescence not only protects mental health concurrently -perhaps partially by diminishing sensitivity to other adversities (101) -but into adulthood as well. Indeed, one study found that a family-based parenting intervention in early adolescence was associated with improved self-regulation (and consequently, vmPFChippocampal functional coupling) at age 25 (102).…”
Section: Contextual Factors Affecting Resiliencementioning
confidence: 99%
“…T here is robust evidence that early experiences of poverty and other forms of early adversity experienced prenatally (1)(2)(3) and/or postnatally (4)(5)(6)(7)(8)(9)(10)(11)(12) contribute to an increased risk for poor developmental outcomes, including mental health problems in childhood and adulthood. The overwhelming evidence of such associations has encouraged efforts aimed at early intervention and prevention (11,13). However, the success of such efforts is contingent upon a better understanding of the mechanisms linking early poverty to poor developmental outcomes.…”
mentioning
confidence: 99%